Genomic mutations after multigenerational exposure of Caenorhabditis elegans to pristine and sulfidized silver nanoparticles. (November 2019) - Wamucho, Anye; Unrine, Jason M.; Kieran, Troy J.; Glenn, Travis C.; Schultz, Carolin L.; Farman, Mark; Svendsen, Claus; Spurgeon, David J.; Tsyusko, Olga V.
Abstract: Our previous study showed heritable reproductive toxicity in the nematode Caenorhabditis elegans after multigenerational exposure to AgNO3 and silver nanoparticles (Ag-NPs). The aim of this study was to determine whether such inheritable effects are correlated with induced germline mutations in C. elegans . Individual C. elegans lineages were exposed for 10 generations to equitoxic concentrations at EC30 of AgNO3, Ag-NPs, and sulfidized Ag-NPs (sAg-NPs), a predominant environmentally transformed product of pristine Ag-NPs. The mutations were detected via whole genome DNA sequencing approach by comparing F0 and F10 generations. An increase in the total number of variants, though not statistically significant, was observed for all Ag treatments and the variants were mainly contributed by single nucleotide polymorphisms (SNPs). This potentially contributed towards reproductive as well as growth toxicity shown previously after ten generations of exposure in every Ag treatment. However, despite Ag-NPs and AgNO3 inducing stronger reproductive toxicity than sAg-NPs, exposure to sAg-NPs resulted in higher mutation accumulation with significant increase in the number of transversions. Thus our results suggest that other mechanisms of inheritance, such as epigenetics, may be at play in Ag-NP- and AgNO3 -induced multigenerational and transgenerational reproductive toxicity. Graphical abstract: Image 1 Highlights: Multigenerational exposure to pristine and sulfidized Ag-NPs increase mutations. Mutations are mainly contributed by single nucleotide polymorphisms. Mutations alone cannot not explain multigenerational reproductive toxicity. Epigenetic mechanisms might be involved in multigenerational toxicity of Ag-NPs. Abstract : Multigenerational exposure to pristine and sulfidized Ag nanoparticles is characterized with overall increases in germline mutations.